Les scieries hydrauliques vosgiennes - Jean-Yves Henry (In Situ)
As part of its thematic investigation of the Vosges mountain’s small hydraulic industrial sites, the General Inventory service of the Lorraine region undertook a study of water-powered saw-mills. More than 250 sites are mentioned in the archives; 115 sites, from slight vestiges to complete saw-mills, were identified in the field and 25 were the subject of individual notices published on the Ministry’s national heritage database, Mérimée. One was listed as a historic monuments, completing a corpus of sites already protected at an earlier date. Certain sites have been known for a long time, protected as historic monuments and exploited as tourist attractions. Others, even though their original machinery might remain, can be found in a state of complete abandon, or, less frequently, restored by private owners and not open to public visits. Still others have suffered from the multiple vicissitudes that affect industrial buildings, being constantly modified and adapted to the needs of the time. Of others, finally‒the majority‒there are only vestiges of the water-power organisation, the buildings having been destroyed by fire or simply replaced by contemporary equipment.